Qur'anic Education in South Western Nigeria in the 21st Century: Challenges and Prospects (Al Basirah, 2025)
This study examines the challenges facing Qur'ān education across the six states (Ekiti, Lagos, Ogun, Ondo, Osun, Oyo) which makes up South-West Nigeria. Qur'ānic education is an elementary knowledge undertaken by Muslim laden and adult to acquire the background knowledge of Al-Qur'ān. It therefore highlights some of the challenges confronting its students, teachers and learning environment and proposes some needs though which these hassles could be solved. The study adopted descriptive, analytical, and phenomenological methods. Our findings reveal that lack of qualified teachers, poor funding, are one of the key challenges affecting the effective learning on the part of the students and teachers, and suggests futuristic prospects for reform. This paper concludes that Qur'ānic education in the region should be given dimensional priorities. It further recommends prospects like creating conducive learning environment, active engagements of parents, employment of competent Qur’anic educators, adequate funding of Qur’anic education schools, provision for curriculum integration, and proper enrollment of students as one of the prospects for Qur’anic education schools in South-western Nigeria.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent:  The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study.Copyright: Author(s) retains the Copyright of this article.
Keywords: Challenges; Prospects; Qur'anic Education; South Western Nigeria; Quranic Education Schools